MEN1 gene mutation with parathyroid carcinoma: first report of a familial case - Luigia Cinque; Angelo Sparaneo; Antonio S Salcuni; Danilo de Martino; Claudia Battista; Francesco Logoluso; Orazio Palumbo; Roberto Cocchi; Evaristo Maiello; Paolo Graziano; Geoffrey N Hendy; David E C Cole; et al. (Endocrine Connections, 2017)
Background: The occurrence of parathyroid carcinoma in multiple endocrine neoplasia type I (MENI) is rare and the 15 cases of malignant parathyroid tumor reported so far have been associated with MENI in individuals and not with multiple members within a family. Methods: We report on a 61-year-old male, operated for a 7.3 cm parathyroid carcinoma infiltrating the esophagus. In his brother, a 4.6 cm parathyroid carcinoma was diagnosed histologically, while in the daughter, neck ultrasonography revealed 2 extrathyroidal nodules, yet to be excised. Results: Screening of the MEN1 gene identified a known germline heterozygous missense mutation (c.1252G>A; p.D418N) in exon 9, in all affected subjects. Conclusions: The occurrence of parathyroid carcinoma in more than one affected member of a single MEN1 family represents the first reported familial case. This suggests that additional constitutional genetic mutations may contribute to the variation in malignant potential and clinical behavior of parathyroid tumors in MEN1.